Optimization of the Process of Forming State Budget Revenues in the Context of Digital Transformation and Improvement of Tax Administration. - Zaynalov, Jahongir; Abdunazarov, Davlat (Journal of Economics and Tourism Research, 2026)
In the context of modern economic reforms in the Republic of Uzbekistan, improving the public finance management system and increasing the effectiveness of fiscal policy are important factors in ensuring macroeconomic stability. Achieving the country’s long-term development goals directly depends on the stable and transparent formation of state budget revenues. Optimizing state budget revenues includes expanding the tax base, reducing the shadow economy, and introducing digital technologies into tax administration. In conditions of global economic uncertainty, making the financial system more flexible is of great importance. From this perspective, a new Tax Code has been adopted in Uzbekistan, and reforms aimed at increasing transparency are being implemented. At the current stage, transitioning to a data-driven management system in the formation of state budget revenues, digitalizing tax authorities, and implementing the “Tax Administration 3.0” concept are considered urgent tasks.